Factor Affecting Insomnia in Ischemic Stroke Patients - Agustina Fajarini; Mukhlisa Mukhlisa; Sri Handayani; Pinto Desti Ramadhoni; Irfannuddin Irfannuddin (AKSONA, 2025)
Highlight: Insomnia is prevalent in ischemic stroke patients and can hinder the recovery process. Stroke patients have a higher prevalence of insomnia and related symptoms than the general population.  This study found a complex relationship between physical, psychological, and social risk factors for insomnia following ischemic stroke.   ABSTRACT Introduction: Insomnia is common in ischemic stroke patients and can negatively impact on the post-stroke recovery process by interfering with the body's natural healing process, reducing the effectiveness of rehabilitation therapy, and affecting the recovery of cognitive function. Effective management and early intervention in  insomnia are needed to enhance health services for stroke patients, promote optimal recovery, and improve their quality of life. Objective: This study aimed to identify and analyze the various factors associated with the occurrence of insomnia among patients with ischemic stroke. Methods: This is a cross-sectional study that used secondary data from medical records and primary data gathered through questionnaire-based interviews. The subjects were 105 ischemic stroke patients at the Neurology Clinic of Dr. Mohammad Hoesin Hospital, Palembang, between May to July 2024. The data acquired for further analysis included social and demographic details, comorbid conditions, depression, anxiety, pain, insomnia, medication use, sleep hygiene, and stroke clinical features. The data was then analyzed using IBM SPSS Statistics 24 and assessed through bivariate and multivariate analyses to evaluate the relationships between variables. Results: The prevalence of insomnia in this study was 42.9%, with mild insomnia observed in 26.7%, moderate insomnia in 13.3%, and severe insomnia in 2.9% of the subjects. Obstructive sleep apnea (OSA) (OR: 22.718), sleep hygiene index (OR: 6.490), and education level (OR: 3.453) were identified as determinants related to insomnia in ischemic stroke patients. Indirect factors associated with insomnia in ischemic stroke patients include depression, the number of comorbid diseases, pain, diabetes, a history of insomnia, anxiety, and stroke onset. Conclusion: There is a complex relationship between various physical, psychological, and social factors and the incidence of insomnia after ischemic stroke.